2020
DOI: 10.1177/2192568220979141
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Symptomatic Spinal Epidural Hematoma Following Posterior Thoracic Spinal Surgery in a Single Institute

Abstract: Study Design: Case-control study. Objectives: To investigate the incidence of symptomatic spinal epidural hematoma (SSEH) and recognize its risk factors in a cohort of patients undergoing posterior thoracic surgery in isolation. Methods: From January 2010 to December 2019, patients who developed SSEH after posterior thoracic surgery and underwent hematoma evacuation were enrolled. For each SSEH patient, 2 or 3 controls who did not develop SSEH and underwent the same procedures with similar complexity at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…In our cohort of patients, we found out that obesity (abnormal level of BMI above 30 kg/m 2 ) is a signifi cant risk factor for the incidence of postoperative symptomatic SEDH. Our fi ndings confi rm previous studies -the incidence of symptomatic SEDH requiring evacuation ranges from 0.1 % to 3.7 % (3,(9)(10)(11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our cohort of patients, we found out that obesity (abnormal level of BMI above 30 kg/m 2 ) is a signifi cant risk factor for the incidence of postoperative symptomatic SEDH. Our fi ndings confi rm previous studies -the incidence of symptomatic SEDH requiring evacuation ranges from 0.1 % to 3.7 % (3,(9)(10)(11).…”
Section: Discussionsupporting
confidence: 91%
“…In the postoperative period, there is an increased risk of impaired wound healing due to low regional perfusion and oxygen tension, infectious complications and last but not least, worsened and limited rehabilitation after surgical procedure (7,8,11,12). From the perspective of spine surgery, if a patient after surgery does not follow an adequate regular rehabilitation and suffi cient physical activity, obesity of the patient leads to a higher risk for recurrence of degenerative spine diffi culties requiring revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors guide surgeons in selecting appropriate procedures and gauging possible complications. Some reported risk factors included obesity, diabetes, advanced age, tumor history, and preoperative steroid use and son on 5,8,19,26. In our study, multivariate analysis indicated that risks of reoperation increased by 2.2 times, 1.9 times, and 1.7 times in patients who underwent upper thoracic spine surgery, got a thoracic kyphosis ≥45°, and suffered from an intraoperative dural tear, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…The surgical sites were divided into cervical [8,10,11,13,14,19,28,36,37,[40][41][42][43][44][45], thoracic [8,11,13,19,28,31,[40][41][42][44][45][46] and lumbar [5, 8, 9, 11, 13, 16-22, 28, 29, 32-35, 40-42, 44-46] surgery with 15, 12 and 25 studies including 27,779, 16,897, 80,766 patients, respectively, and 72, 104 and 356 patients developed SSEH, respectively. The pooled incidence of SSEH was 0.32% (95% CI 0.002-0.005, P < 0.01, I 2 = 63%) for cervical surgery, 0.84% (95% CI 0.004-0.017, P < 0.01, I 2 = 88%) for thoracic surgery, and 0.63% (95% CI 0.004-0.010, P < 0.01, I 2 = 92%) for lumbar surgery.…”
Section: Surgical Sitementioning
confidence: 99%